Apparent or real water exchange reactions on [Zn(H 2O) 4(L)] 2+·2H 2O (L = sp-nitrogen donor ligands)? A quantum chemical investigation - Alzoubi, Basam; Walther, Markus; Puchta, Ralph; van Eldik, Rudi (Dalton Transactions, 2012)
The exchange of a second coordination sphere water molecule in [Zn(H 2O) 4(L)] 2+·2H 2O (L = HN 3, HCN, FCN, ClCN, BrCN, CH 3CN, (C 4H 3)CN, PhCN, (CH 3) 3CCN, CF 3CN, CCl 3CN, CHCl 2CN, and CH 2ClCN) against a coordinated water molecule was studied by quantum chemical calculations (RB3LYP/6-311+G**). The complete reaction consists of an associative binding of one H 2O from the second coordination sphere leading to a six-coordinate intermediate [Zn(H 2O) 5(L)] 2+·H 2O, followed by the dissociation of a water molecule to reach the product state [Zn(H 2O) 4(L)] 2+·2H 2O. For a real water exchange reaction to occur two different transition states have to be included, otherwise only an apparent water exchange reaction takes place. For the water exchange reaction in [Zn(H 2O) 4(L)] 2+·2H 2O, nearly iso-energetic cis- and trans-orientated transition states are crossed. The gas-phase proton affinity of L shows instructive correlations with structural parameters and energy gaps for the investigated reactions. © 2012 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2026-01-22